Labor performance as an occupational vector - Grijalva Medina, Micaela; Guamán Andino, Melanie; Castro Analuiza, Juan (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December), 2019)
With the performance issue the 56% of Ecuadorian workers belong to the food and beverage place do their activities optimally, with all this, it was necessary evaluating chores and functions of the workers with job performance related factors, this motivated to do a previous diagnosis for the four dimensions assessment: attitude, personality, perception and learning of the foo company worker. Thus a quantitative non experimental, cross character and relational reach study was done that enhanced the job performance and the four dimensions association, all of this these were evaluated by a self-administered test to 53 employees, with 12 Likert scale adapted questions adapted to Dacum Method, to realize the related factors with the job performance. Finally, the result indicates that the variables with the most significance is the way the bosses treat their workers (rho = 0.464) and the process work (rho = 0.400) that are in the learning and perception dimensions, these two generate a stable organizational climate and let the developing skills, innovate and adapt the change.